1985
DOI: 10.1128/jcm.21.5.796-799.1985
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three bacteriuria screening methods in a clinical research hospital

Abstract: In a study conducted to compare three screening methods for their ability to detect significant bacteriuria, 2,815 urine specimens were screened by Chemstrip LN (BioDynamics, Division of Boehringer Mannheim Chemicals, Indianapolis, Ind.), 1,000 were screened by Bac-T-Screen (Marion Scientific Laboratory, Kansas City, Mo.), and 289 were screened by ATP assay (Turner Designs, Mountain View, Calif.). Results were compared with those obtained by quantitative culture plate method. The ATP assay showed the highest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
1

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…A closer examination of the 24 false negatives revealed that 9 (37.5%) were clinically significant in that in each case the preceding and/or the following culture was also positive for the same organism. Bearing in mind the possible impact of missing these nine cases on patient morbidity (9), we consider that the use of UF-100 and urine strip results to screen urine samples for UTI is not advisable. Although they did not state it clearly, Okada et al (8) came to the same conclusion with regard to screening for UTI by using UF-50.…”
mentioning
confidence: 99%
“…A closer examination of the 24 false negatives revealed that 9 (37.5%) were clinically significant in that in each case the preceding and/or the following culture was also positive for the same organism. Bearing in mind the possible impact of missing these nine cases on patient morbidity (9), we consider that the use of UF-100 and urine strip results to screen urine samples for UTI is not advisable. Although they did not state it clearly, Okada et al (8) came to the same conclusion with regard to screening for UTI by using UF-50.…”
mentioning
confidence: 99%
“…Several studies have been made on the use of reagent strips as a rapid method to indicate the presence of urinary tract infection and renal disease.' 14 Most of these methods, however, have used the detection of leucocyte esterase, or nitrite, or a combination of both, and have been performed on unselected patient populations. To date no studies have been carried out specifically on paediatric patients.…”
mentioning
confidence: 99%
“…Urine cultures represent 40 to 70% of the specimens sent for examination to clinical-microbiology laboratories (7,14). Although the prevalence of urinary infections may vary in different patient populations, approximately 80% of urine cultures are negative (7,14,33). In an attempt to reduce the cost and time expended in examining these negative cultures, several rapid methods have been developed for characterizing bacteriuria, including microscopic examination, chemical tests, and automated systems (6,7,17).…”
mentioning
confidence: 99%